Suggestions from Antiquity. Discovering Classical Iconographies in the Trecento Divine Comedy Illustrations - Ponchia, Chiara (Actual Problems of Theory and History of Art, 2015)
After Dante’s death (1321), the Divine Comedy quickly became one the most appreciated works of Italian literature. Its spreading was impressively wide, since from the first half of the 14th century patrons asked for illuminated manuscripts of the poem, looking for a visual support to imagine Dante’s pilgrimage through the Hereafter. Therefore, illuminators had to face the difficult challenge of illustrating the text with no previous iconographic tradition. The easiest way to deal with this issue was turning to other sources, choosing among them the most suitable iconographies to be re-used in Dante’s masterpiece illustration. In this article we will see that, just as Dante’s literary sources were both mediaeval and classical, the illuminators’ quest for images wasn’t limited to contemporary sources, and in some cases we might find the echo of Сlassical models in the Divine Comedy illustrations.
Keywords: history of illuminated manuscripts; Divine Comedy; Italian illumination; mediaeval art; iconography and iconology; Classical heritage